Analysis of Customer Satisfaction Towards Employee's Work Performance in McDonald's Zapote Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Filipinos are always on the go, though there are dining restaurants all around, sometimes, ormost often, they prefer affordable and quick orders of fast food. It is often visible at birthdayparties or cheap group meals, and by observation, which can tell that their service will alwaysbe in demand, especially in the Philippines, where most cannot afford luxury in expensiverestaurants.Respondents had an effect on the portion size of food and had a problem with the speed ofservice, employee greetings, and the sound level of the branch and in giving information to thecustomer. Most of the respondents had a problem with their manager's feedback. Findingsshow that the respondents have an equal result. They do not have any problem with theirprofessionalism but are having a problem with going to work with excitement.McDonald’s should make their food servings bigger, like “what you see is what you get” ontheir menu. Employees should entertain the customer politely and always keep smiling in frontof the customer so that the customer won’t hesitate to ask the employee something.McDonald’s should provide a relaxing playlist so that the customer can relax while dining.McDonald’s employees should exercise every morning before they open the store so that theywill not get exhausted and be more energetic. Employees of McDonald’s should be committedto what they’re doing in their workplace for them to achieve customer satisfaction.
Keywords: Hospitality Management